Observation and Implications of Composition Inhomogeneity Along Grain Boundaries in Thin Film Polycrystalline CdTe Photovoltaic Devices. Issue 16 (1st July 2019) - Misra, Sudhajit; Aguiar, Jeffery A.; Sun, Yubo; v. Devener, Brian; Palekis, Vasilios; Ferekides, Christos S.; Yoon, Heayoung P.; Bermel, Peter; Scarpulla, Michael A.
Abstract: Leading photovoltaic technologies such as multicrystalline Si, CdTe, Cu(In, Ga)Se2, and lead halide perovskites are polycrystalline, yet achieve relatively high performance. At the moment polycrystalline photovoltaic technologies stand at a juncture where further advances in device performance and reliability necessitate additional characterization and modeling to include nanoscale property variations. Properties and implications of grain boundaries are previously studied, yet chemistry variations along individual grain boundaries and its implications are not yet fully explored. Here, the effects of bromine etching of CdTe absorber layers on the nanoscale chemistry are reported. Bromine etching is commonly used for improving CdTe back contacts, yet it removes both cadmium and chlorine along grain boundaries to depths closer to 1 µm. 2D device simulations reveal these composition modifications limit photovoltaic performance. Since grain boundaries and their intersections with surfaces and interfaces are universal to thin film photovoltaics, these findings call for similar studies in each of the photovoltaic technologies to further enable advances. Abstract : Effects on interface chemistry following bromine etching in CdTe absorber layers are investigated. Bromine etching is commonly used for improving back contacts in photovoltaics, yet this process preferentially removes cadmium and chlorine along grain boundaries to micrometer‐scale depths. This work therein reports bromine etching is deleterious to CdTe and can easily be extended to other thin film photovoltaics.